Identification of Suitable Land for Livestock Production Using GIS-Based Multicriteria Decision Analysis and Remote Sensing in the Bale Lowlands, Ethiopia. (3rd October 2022) - Balew, Abel; Legese, Behailu; Kunbushu, Derara; Nega, Worku; Alebel, Wubshet; Kerbesh, Abebe; Mijanur Rahman, Md.
Abstract : Rangeland resources of the Bale lowlands have been degraded due to climate change, human factors, lack of sufficient environmental and rangeland policies, disaster mitigation strategies, and good management. The study identified suitable rangeland for cattle, sheep, goat, and camel production in the Bale lowlands using GIS-Based Multicriteria Decision Analysis and remote sensing techniques. Land-use and land-cover, rainfall, water accessibility, slope, and soil types were used for the suitability analysis. The study showed that an area of 4112, 16311, 6643, and 9820 km 2 was highly suitable for cattle, sheep, goats, and camels, respectively. The results of the study also indicated that an area of 40099, 30925, 41981, and 36802 km 2 was moderately suitable for cattle, sheep, goats, and camels, respectively. In addition, an area of 7644, 4671, 3630, and 5632 km 2 was marginally suitable for cattle, sheep, goats, and camels, respectively. On the other hand, an area of 399 and 346 km 2 was not suitable for cattle and sheep, respectively. The study is important for improving livestock production and mitigating the impacts of traditional livestock mobility on local communities. The study can also provide insights for government authorities to formulate environmental and rangeland policies to identify rangeland types and separate the rangeland for each livestock category.